Increasing Family Child Care Providers' Professionalism through Certification and a Professional Network - Robinson, Louester A. S. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1999)
Noting that in many areas, family child care providers lack both available training to enhance their professional skills and an organized professional network for continual support, this practicum project implemented and evaluated the effectiveness of a curriculum to prepare family child care providers for state certification through a community college setting in a southeastern state. Participants who received the credential for family child care also formed a resource and referral network, a lending library, and a professional association for family child care providers serving the same counties as the college. Training was provided in 12 sessions on topics including health and safety, building partnerships with families, observing young children, guiding children's behavior, children's special needs, marketing and advocacy, and licensing and regulations. Also, part of the program was an 8-month implementation tracking process for training and licensing. Home visits were provided on an individual basis, and additional training was provided on cardiopulmonary resuscitation and first aid. Analysis of data from the project indicated that the following anticipated outcomes were obtained: (1) participants became knowledgeable through curriculum designed for family child care providers; (2) participants increased their knowledge in how to access resources and referrals within the college setting; and (3) participants became knowledgeable in how to meet requirements for operating a licensed family day care home. (Six appendices include data collection instruments. Contains 50 references.) (KB)
ERIC Note: Ed.D. Practicum II Report, Nova Southeastern University.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Caregiver Training; Certification; Child Caregivers; Early Childhood Education; Family Day Care; Knowledge Level; Professional Development; Program Effectiveness; Program Evaluation; Training Methods; Two Year colleges; Caregiver Qualifications -- Professionalism; Dissertations/Theses, Practicum Papers